An Overview on Energy Harvesting Using Piezoelectric Material for Wi-Fi Systems - Heena T. Shaikh; IR. Kazi Kutubuddin Sayyad Liyakat (International Journal of Electro-Mechanics and Material Behaviour, 2026)
The rapid proliferation of wireless-networked devices has intensified the demand for sustainable, maintenance-free power sources that can keep small-scale Wi-Fi modules operational in hard-to-reach or infrastructure-limited environments. This study investigates the feasibility of harvesting ambient mechanical energy using piezoelectric transduction technology and directly feeding the harvested power to a low-power Wi-Fi communication subsystem. A compact energy-harvesting module was engineered from lead-zirconate-titanate (PZT) cantilevers with resonant frequencies tuned to the dominant vibration spectra encountered in indoor office settings (≈ 20–80 Hz). The harvested alternating-current (AC) signal was conditioned by a synchronous-rectifier-based power-management integrated circuit (PMIC) that delivers a regulated 3.3 V DC rail. The Wi-Fi transmitter, implemented on an ESP-32 platform and operated in a duty-cycled “beacon-only” mode, consumes an average of 120 µW during active transmission bursts of 5 ms at 100 ms intervals. Laboratory tests demonstrate that a single PZT cantilever, exposed to a modest 0.5 g vibration amplitude, can generate up to 250 µW, enough to sustain the transmitter indefinitely under the chosen duty cycle. Field trials in an office corridor and a subway platform confirm stable operation over 48 h with no external power input, while the harvested energy simultaneously powers a miniature environmental-sensing node. These results validate piezoelectric harvesting as a viable, self-sufficient energy source for low-throughput Wi-Fi IoT devices, opening a pathway toward truly battery-free wireless sensor networks.
Keywords: Energy harvesting; Harvesting; Piezoelectric material; Wi-Fi; battery; energy